Comparison of the Effectiveness of Four Scoring Techniques in Secondary School Multiple-Choice Test Items in Financial Accounting - Fadipe, Olaitan Isaac; Faremi, Yinusa A. (Mediterranean Journal of Social Sciences, 2021)
Poor academic performance of students in senior secondary school certificate examination in some commercial subjects may be attributed to ineffective scoring techniques used by classroom teachers and examination bodies. Therefore, this study compared the effectiveness of four scoring techniques in multiple-choice financial accounting in secondary schools of Osun state, Nigeria. The study adopted a descriptive survey and Quasi-experimental research designs. The sample consisted of 420 senior secondary schools (SSSII) Financial Accounting students selected using Multi-stage sampling technique. An instrument titled â€œFinancial Accounting Multiple-Choice Test (FAMT)â€ with a reliability coefficient of .80 was administered to selected students. The marks obtained through standard conventional, logical weight, corrected and confidence scoring techniques were analyzed using descriptive and inferential statistics. Findings showed that the logical weight scoring technique had the highest mean value of 40.63 when compared with other scoring techniques. It was also revealed that there was a significant difference in the performance of students in Financial Accounting multiple-choice test items using the four scoring techniques (F(3,1676) =31.494, p<.05). Based on the findings, it was concluded that students performed better using the logical weight scoring technique in Financial Accounting multiple-choice test items and is the most effective scoring technique among others. The study recommended that a logical weight scoring technique should be encouraged and used in scoring Financial Accounting multiple-choice test items in secondary schools by examination bodies. Received: 27 March 2021 / Accepted: 29 April 2021 / Published: 17 May 2021